The ghostly horror of the banal or La primera vez que vi un fantasma - Cervera Salinas, Vicente (Anales de Literatura Hispanoamericana, 2019)
This paper analyzes the tales or short stories that integrate the volume of Ecuadorian writer Solange Rodríguez Pappe, La primera vez que vi un fantasma, published in 2019. The stories are inserted in a double tradition: the European and the Spanish-American itself, where the names of Miguel Ángel Asturias and Juan José Arreola are decisive for the activation of the symbolic and thematic resources of this recent narrative of the fantastic or, according to new critical catalogs, of the "unusual."